GP169 The pocket-money study. (June 2019) - Flinn, K; Healy, E; O'Riordan, A; Fitzgerald, E; Lineen, C; O'Gorman, C; Murphy, AM
Abstract : Background and aims: Pocket-money is generally accepted to be a means for parents to introduce concepts of self-management, saving, budgeting and responsibility for their children. Much of the available published research focuses on the philosophical and sociological impact of pocket-money on the child's autonomy and on the dialogue between the parents' value systems or work ethic and how they confer this on their children. Previous research has found that pocket-money is a simple way of preparing children for the future and creating more financially literate adults. 1 From a paediatric-research viewpoint, pocket-money is considered a minor variable to be assessed when examining the broader picture of children's negative health habits. There is a dearth of information available worldwide in either the medical literature or contemporary media on the amount children receive as pocket-money, how they spend it, how they should spend it and the consequences of the above. Our objective was to investigate the practices of a cohort of modern-day parents in Ireland regarding the administration of pocket-money to their children in terms of ethos, amount, frequency and supervision. We also explore the potential contribution a 'pocket money culture' makes to today's societal problems – obesity-pandemic, addiction-culture and materialism. Methods: A specifically designed questionnaire was administered to a random selection of 50 parents of children (≤18 years of age), attending our institution during August and September 2018. Data was compiled and analysed using Excel and SPSS. Results: A total of 50 questionnaires pertaining to 116 children (61 boys, 55 girls), were collected (4 fathers, 45 mothers, 1 grandmother). Only 19 guardians gave their children regular pocket money. Reasons cited were overall cost of living and a sense of already providing what is needed. Conclusion: To our knowledge it is the first study of its kind in Ireland. Further studies are needed to review changing mores with regard to pocket-money that may have arisen as result of the recession and the potential impact of this on parenting and childhood in Ireland. References: Sansone D, Rossi M, Fornero E. 'Four Bright Coins Shining at Me': Financial Education in Childhood, Financial Confidence in Adulthood. Journal of Consumer Affairs [Internet] 2018;. Available from: https://onlinelibrary.wiley.com/doi/abs/10.1111/joca.12207